Examination of capital structure decisions: evidence from UK listed firms - Fan, Jiahui (2010)
In this paper, we attempt to analyses the determinants of capital structure in the UK. Besides, we also examine the empirical results compared with the implication of past capital structure theories and research. The panel data model with a sample of 100 non-financial listed firms in the United Kingdom between 1999 and 2008 is conducted to test the hypotheses. We use proxy variables that suggested by past literatures to explain capital structure decisions of the UK firms.